Evaluasi User Experience Genre Beat'em Up 2Dimensi(2D) Pada Game PawPawPaw dari Simpleton Studio Menggunakan Metode Game Experience Questionnaire (GEQ) - Ilmam Achmadiarsyi; Komang Candra Brata; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Simpleton Studio is a game developer from Indonesia who has released several games. Simpleton Studio is developing a new game called PawPawPaw which requires an evaluation of the user experience before being released. The method used in this study is the Game Experience Questionnaire with a questionnaire-based instrument with the aim of knowing the dimensions that are less targeted to the user. This Game Experience Questionnaire method has 3 modules. The first module is the Core Module which produces an average value above 3 in the Competence, Immersion and Positive Effect dimensions and the lowest value is in the Negative Effect dimension. The second module is the Social Presence Module which produces an average score above 3 for the dimensions of Psychological Involvement - Emphaty and Behavioral Involvement and the lowest score is on Psychological Involvement - Negative Feelings. The third module is the Post-Game Module which produces the highest score on the Positive Experience dimension and the lowest score on the Negative Experience and a high enough score on the Tiredness dimension. It can be concluded that the user experience of the PawPawPaw game is quite good, but there are several problems because the game is easy to forget and quite tired after playing.